Pengaruh Fasilitas Kerja dan Pengembangan Karir terhadap Kepuasan Kerja Serta Dampaknya pada Kinerja Pegawai pada Sekretariat Daerah Kabupaten Tanjung Jabung Barat - Hartanto, Erwin; Suryani, Arna; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2025)
This research aims to understand and describe the condition of work facilities, career development, job satisfaction and employee performance at the Regional Secretariat of West Tanjung Jabung Regency, as well as analyzing the influence of work facilities and career development on employee performance through the mediation of job satisfaction. This research is descriptive verification with a PLS analysis approach. The survey results show that work facilities are in the good category with a total score of 6027. Employee career development is also rated as good with a score of 3624. Employee job satisfaction is classified as satisfied with a total score of 4175, while employee performance is recorded as high with a score of 6414. Research findings reveal that work facilities and Career development has a positive and significant influence on job satisfaction. Apart from that, both of them also directly influence employee performance positively and significantly. Job satisfaction itself is proven to be a mediating variable that strengthens the relationship between work facilities and career development and employee performance.